Tracing Triggers from Intern Islamic Conflict: Case Study of Syi’ah-Sunni in Indonesian - Ade Jamarudin; Asmal May (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
Syi'ah is a group of Muslims who believe that sayyidina Ali ra. is a person who has the right to be a successor to the prophet, because the Prophet SAW. willed that his successor after death was sayidina Ali bin Abi Talib. The existence of new streams that emerge at this time is some of the other schools that are a challenge from the previous one too, from time to time and continue to always be there. Until now the above phenomenon cannot be avoided. Freedom of religion is an open choice for the community that leads to the progress of democracy. testament delivered by the Prophet Muhammad to